E-Effectiveness Musrembang's in the Development Planning Process in Medan's Denai District - Siti Hazzah Nur Ritonga; Humaizi Humaizi (Jurnal Administrasi Publik (Public Administration Journal), 2021)
In the regional development planning process, there are frequently deviations in people's aspirations. Musrenbang is a community forum for channeling aspirations in development planning. The launch of the e-musrembang application is expected to accommodate all community aspirations, allowing regional development to be more focused on the community's actual needs. This research aims to determine the efficacy of e-musrembang in development planning in Medan City and the problems or obstacles encountered when using the application. Using qualitative research methods, this study focuses on the Medan Denai District. Interviews, observation, and documentation were used as data collection techniques. Miles, Huberman, and Saldana's interactive analyses were used to analyze the data. The study's findings concluded that had not been effectively implemented the e-Musrenbang system. There is no significant difference between the achievement of the e-Musrenbang system's objectives and the implementation b From the achievement of the purposes of the e-Musrenbang system, and there is no significant difference from the implementation before after the e-Musrenbang. Citizens' misunderstanding in the e-Musrenbang system is judged due to the lack of good communication between the government and its citizens. In the adaptation stage, the Kelurahan and Medan Denai Subdistrict Governments, as implementers in the use of the system, are still rigid and do not understand well the use of the e-Musrenbang system.